CURRENT CIRCULATION STUDY OF KARIMUNJAWA ARCHIPELAGO USING DELTF3D MODEL - Ilham, Mohammad
Karimunjawa Archipelago is a Marine National Park which is one of Indonesia's marine tourism objects. With that status, Karimunjawa Archipelago waters have numerous potentials and unique characteristics. Despite the potentials of the area, there isn’t sufficient related research about the Oceanographic conditions of the area. This research focuses on the hydrodynamic characteristics, spesifically tides and tidal currents of Karimunjawa Archipelago waters which located in Jepara, Central Java. This research is conducted using DELFT3D hydrodynamic model. The simulation is done using only tides as the generating force. The required datas are acquired from Tide Model Driver (TMD) for tides, National Bathymetry (BATNAS) of Geospatial Information Agency (BIG) for bathymetry, and obeservation data of tides for model verification. Harmonic analysis is utilized to determine the tidal type and current circulations are plotted spatially. The simulation returns an RMSE of 0.06 m, percent error of 8,32 %, and Aida number. Referring to the Formzahl number of 2.81, it can be determined that the tidal type of the area is mixed prevailing diurnal. The dominant constituent is found to be K1 with an amplitude of 0,25 – 0,45. Of the four components, components K1, M2, and S2, spread from Karimunjawa Island to Nyamuk Island, while O1 component spreads in the oppsite direction. Maximum average velocity of the tidal current reaches 0,136 m/s, flowing from east to west from low water en route to high water and low water water and reversing in direction from west to east on high water en route to low water and high water condition.